2007
DOI: 10.1021/es0704176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidity on Secondary Organic Aerosol Formation from Isoprene

Abstract: The effect of particle-phase acidity on secondary organic aerosol (SOA) formation from isoprene is investigated in a laboratory chamber study, in which the acidity of the inorganic seed aerosol was controlled systematically. The observed enhancement in SOA mass concentration is closely correlated to increasing aerosol acidity (R2 = 0.979). Direct chemical evidence for acid-catalyzed particle-phase reactions was obtained from the SOA chemical analyses. Aerosol mass concentrations for the 2-methyltetrols, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
496
4
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(540 citation statements)
references
References 37 publications
(92 reference statements)
38
496
4
2
Order By: Relevance
“…The ESI tandem MS was operated with nebulizer pressure at 0.8 bar and a dry gas flow of 10 L min −1 . A solution of camphor sulfonic acid (Sigma-Aldrich, USA) was used to optimize ionization and fragmentation parameters to gain high intensity of [M−H] − , the resulting ionization voltage was 4 kV and the fragmentor was 120 V. 34 S-containing isotopic peaks coincident with the target ions provided an additional confirmation of 32 Scontaining formulas. 35 For pNOSs, additional MS/MS product ions with m/z 247 (loss of HNO 2 ) and m/z 231 (loss of HNO 3 ) were detected.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ESI tandem MS was operated with nebulizer pressure at 0.8 bar and a dry gas flow of 10 L min −1 . A solution of camphor sulfonic acid (Sigma-Aldrich, USA) was used to optimize ionization and fragmentation parameters to gain high intensity of [M−H] − , the resulting ionization voltage was 4 kV and the fragmentor was 120 V. 34 S-containing isotopic peaks coincident with the target ions provided an additional confirmation of 32 Scontaining formulas. 35 For pNOSs, additional MS/MS product ions with m/z 247 (loss of HNO 2 ) and m/z 231 (loss of HNO 3 ) were detected.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In contrast, pNOSs are formed by heterogeneous reactions on acidic particles. 9,34,57 High sulfate levels would promote pNOSs' formation. 26 Since there was no significant difference in aerosol acidity between summer and fall (p > 0.05), aerosol acidity should not be the major factor leading to the seasonal differences in correlations between terpenoic acids and pNOSs.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatic peroxy radicals (RO 2 ) react with HO 2 under low NO x conditions to form non-volatile SOA while they reacted with NO under high NO x conditions to form semi-volatile SOA. In addition, the Base model treats the acid enhancement of isoprene SOA (Surratt et al, 2007) and irreversible particle-phase oligomerization (Kalberer et al, 2004), which converts semi-volatile condensed-phase species into non-volatile species. We do not consider SOA formation from IVOCs or via aqueous-phase processing.…”
Section: Base Soa Modelmentioning
confidence: 99%
“…chamber research. Studies have shown that the mass of SOC and the acidity of laboratory-generated aerosol exhibited a linear relationship (Surratt et al, 2007). In this study, the relationship between WSOC and acidity was explored for the purpose of providing the direct evidence for enhanced WSOC formation at high level of acidity in the field-based research.…”
Section: àmentioning
confidence: 99%